Study of the mechanism of antibacterial action of 1,4-di- and 1,4,5-trisubstituted 1Н-1,2,3-triazoles by molecular modeling - Verbilo, Cyril M.; Zuraev, Alexander V.; Grigoriev, Yuri V.; Budevich, Vladislav A.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2020)
The target for antibacterial action of 1,4-di- and 1,4,5-trisubstituted 1H-1,2,3-triazoles against E. coli ATCC 25922 and S. aureus ATCC 6538 was proposed. Structures of target proteins and investigated triazoles were built using molecular modeling. Binding mechanism was suggested according to conducted docking studies. Suggested binding models and affinity for a binding site of 1,4-disubstituted 1H-1,2,3-triazoles correlated with their experimental activity. Further functionalization directions for continuation of a search for a novel effective antibacterial agents were discovered.
Keywords: molecular modeling; docking; antibacterial activity; E. coli; S. aureus; 1Н-1,2,3-triazoles